MEDICO-LEGAL ASPECTS OF THE PHYSICIAN'S RESPONSIBILITY EXPERTISE - Antović, Aleksandra; Zdravkovic, Miodrag; Miljkovic, Milica; Milić, Miroslav; Nikolic, Marija; Pinterovic, Bogdan (Acta medicae Medianae, 2025)
Legal medicine, an independent scientific medical discipline, is crucial in studying and resolving numerous health, legal, and social issues that can harm health or destroy lives. The institution of medico-legal expertise intricately links this science with the field of law. Questions related to medical ethics and the professional, criminal, and civil liability of doctors and other medical personnel are prevalent in forensic medical expertise. The nature of the medical profession implies that healthcare workers perform activities according to the valid healthcare doctrine and the code of professional ethics, which presuppose the assumption of profound professional, ethical, criminal, and material responsibility for their actions. Part of the regulations for malpractice are implemented through the competencies of the health institutions where the health worker is employed, and the work is done through the competencies of the state or public powers transferred by the state to the chambers of health workers, which regulate the obligations and responsibilities in the actions of healthcare workers. In the broadest sense, doctors and medical staff can be held responsible if they break humanitarian principles, universal human rights, established and generally accepted scientific medical achievements and rules of the professional code at a given time (lat. Vitium Artis).
Keywords: medical malpractice, physician's responsibility, forensic medicine, medicolegal expertise